1995
DOI: 10.1093/clinchem/41.5.700
|View full text |Cite
|
Sign up to set email alerts
|

Advances in genosensor research

Abstract: Microfabricated devices containing arrays of nucleic acid hybridization sites, known as genosensors, are being developed for a variety of uses in genomic analysis. A great deal of the overall genosensor development effort involves optimization of experimental conditions in the actual use of genosensors. Here we describe a "low-tech" form of genosensor technology, involving arrays of oligonucleotides on glass microscope slides, which can be used to define optimal operating conditions and to develop applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…The advent of DNA arrays has resulted in a paradigm shift in detecting sequence variations and monitoring gene expression levels on a genomic scale (Beattie et al, 1995;Brown & Botstein, 1999;Chee et al, 1996;Cronin et al, 1996;DeRisi et al, 1996;Drobyshev et al, 1997;Eggers et al, 1994;Gunderson et al, 1998;Guo et al, 1994;Hacia, 1999;Hacia et al, 1996;Kozal et al, 1996;Pease et al, 1994;Schena et al, 1996;Shalon et al, 1996;Southern et al, 1999;Yershov et al, 1996;Zhu et al, 1998). DNA chips designed to distinguish single nucleotide differences are generally based on hybridization of labeled targets (Beattie et al, 1995;Chee et al, 1996;Cronin et al, 1996;Drobyshev et al, 1997;Eggers et al, 1994;Guo et al, 1994;Hacia et al, 1996;Kozal et al, 1996;Parinov et al, 1996;Sapolsky et al, 1999;Wang et al, 1998;Yershov et al, 1996) or polymerase extension of arrayed primers (Lockley et al, 1997;Nikiforov et al, 1994;Pastinen et al, 1997;Shumaker et al, 1996). While DNA chips based on these two formats can con®rm a known sequence, the similarities in hybridization pro®les create ambiguities in distinguishing heterozygous from homozygous alleles (Beattie et al, 1995;Chee et al, 1996;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of DNA arrays has resulted in a paradigm shift in detecting sequence variations and monitoring gene expression levels on a genomic scale (Beattie et al, 1995;Brown & Botstein, 1999;Chee et al, 1996;Cronin et al, 1996;DeRisi et al, 1996;Drobyshev et al, 1997;Eggers et al, 1994;Gunderson et al, 1998;Guo et al, 1994;Hacia, 1999;Hacia et al, 1996;Kozal et al, 1996;Pease et al, 1994;Schena et al, 1996;Shalon et al, 1996;Southern et al, 1999;Yershov et al, 1996;Zhu et al, 1998). DNA chips designed to distinguish single nucleotide differences are generally based on hybridization of labeled targets (Beattie et al, 1995;Chee et al, 1996;Cronin et al, 1996;Drobyshev et al, 1997;Eggers et al, 1994;Guo et al, 1994;Hacia et al, 1996;Kozal et al, 1996;Parinov et al, 1996;Sapolsky et al, 1999;Wang et al, 1998;Yershov et al, 1996) or polymerase extension of arrayed primers (Lockley et al, 1997;Nikiforov et al, 1994;Pastinen et al, 1997;Shumaker et al, 1996). While DNA chips based on these two formats can con®rm a known sequence, the similarities in hybridization pro®les create ambiguities in distinguishing heterozygous from homozygous alleles (Beattie et al, 1995;Chee et al, 1996;…”
Section: Introductionmentioning
confidence: 99%
“…DNA chips designed to distinguish single nucleotide differences are generally based on hybridization of labeled targets (Beattie et al, 1995;Chee et al, 1996;Cronin et al, 1996;Drobyshev et al, 1997;Eggers et al, 1994;Guo et al, 1994;Hacia et al, 1996;Kozal et al, 1996;Parinov et al, 1996;Sapolsky et al, 1999;Wang et al, 1998;Yershov et al, 1996) or polymerase extension of arrayed primers (Lockley et al, 1997;Nikiforov et al, 1994;Pastinen et al, 1997;Shumaker et al, 1996). While DNA chips based on these two formats can con®rm a known sequence, the similarities in hybridization pro®les create ambiguities in distinguishing heterozygous from homozygous alleles (Beattie et al, 1995;Chee et al, 1996;Eggers et al, 1994;Kozal et al, 1996;Southern, 1996;Wang et al, 1998). To overcome this problem, several methods have been proposed, including the use of: (i) two-color¯uorescence analysis (Hacia et al, 1996(Hacia et al, , 1998a; (ii) a tiling strategy that uses 40 overlapping addresses for each known polymorphism (Cronin et al, 1996); (iii) incorporation of nucleotide analogues in the array sequence (Guo et al, 1997;Hacia et al, 1998b); and (iv) adjacent cohybridized oligonucleotides (Drobyshev et al, 1997;Gentalen & Chee, 1999;Yershov et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A total of three capture probes were designed, comprising of one for each possible HPV-18 variant ( Table 1 ). The capture probes, including the 3′-aminolink (3′-aminopropanol) modification for covalent attachment to the glass slide surface [ 24 26 ], were purchased from Integrated DNA Technologies Inc. (Coralville, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Before hybridization, slides were blocked by soaking for 1 h at room temperature with a solution comprised of 10 mM tripolyphophate, washed with H 2 O and then air-dried [ 24 ]. This attachment procedure resulted in a surface density of oligonucleotides attached to glass using the 3′-aminopropanol method (10 10 –10 11 molecules/mm 2 ), which corresponds to intermolecular spacing of about 30–100 Å across the surface [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The diameter, geometric shape, and direction of the pores depend on surface orientation, doping level and type, temperature, the composition of the etching solution, and the current density [8,9] . Porous silicon has been employed as a large surface area matrix for immobilization of a variety of biomolecules including enzymes,4 DNA fragments [10] , and antibodies [11] . Moreover, we recently showed that the electronic or optical properties of porous silicon can also be used as the transducer of biomolecular interactions, thus qualifying its utility in biosensor applications [12,13] .…”
Section: Introductionmentioning
confidence: 99%